Concurrence and Co-evolution: The Impact of Global Streaming Services (Netflix) and National Platforms (Megogo, Sweet.TV) on the Transformation of the Ukrainian Audiovisual Market Amidst the Full-Scale Invasion - Katerynych, Petro; Volobuieva, Anastasiia (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2026)
Since the onset of Russia’s invasion of Ukraine, streaming video has emerged as both a cultural lifeline and a battleground for soft power. Utilizing data from a nationally weighted CAWI survey conducted in March–April 2024 (N = 1,167) and six interviews, this article examines the co-evolution of global Netflix and Ukrainian platforms Megogo and Sweet.TV under the pressures of wartime. The weekly reach of domestic streaming services increased from 46% prior to the war to 68%, primarily driven by the availability of Ukrainian-language content and a newly validated Patriotic Streaming Preference Scale (α = 0.88), where a one-standard-deviation increase nearly doubles the likelihood of adopting a local service. Factors such as exclusive sports content, rapid dubbing cycles, and telecom bundling further stabilize the domestic market share, while Netflix reduces subscriber churn by “speaking Ukrainian”: simultaneously dubbed originals remain in the platform’s national top 10 list 38% longer than titles with only subtitles. Meanwhile, piracy decreased by fifteen percentage points as viewers transitioned to legal, local-language catalogues. These findings position Ukraine as a live case study of crisis-accelerated media glocalization and a model for post-war cultural policy.